Everything you need to know to survive teaching - Teacher, Ranting (London ; New York : Continuum, 2005)
The warning as you enter www .rantingteacher.co.uk reads: 'If you are easily offended, think the sun shines out of your kid's behind, or are the chief inspector for schools, you'd better stop right here.' This very much sets the tone for the website - and for this book - a collection of the top 50 teacher's rants and ways of overcoming them.
Introduction; On your marks: The Trials of Training; Get Set: Theory into Practice; Go: The Art of Teaching; Children Can be the Most Irritating Things; In Addition to Teaching; Money's Too Tight to Mention; Dealing with Colleagues; Dealing with Parents; Conclusion; Full Contents; Introduction: Why do you want to be a teacher? 1. On your marks: The trials of training; - The peculiar process of interviewing; - Incentives to train; - The mentor - make or break time; 2. Get set: Theory into practice; - Firm but fair; - Preventing misbehaviour; - Mixed abilities; - Impressing the inspectors; 3. Go: The art of teaching; - The lesson introduction; - The lesson in progress; - The lesson plenary; - irritating interruptions; - Learning Support Assistants; - Incorporating ICT; - Incorporating communication skills; 4. Children can be the most irritating things; - Playing truant; - Language matters; - Well versed in the art of lying; - Classroom banter; 5. In addition to teaching; - Form time; - Covering for a colleague; - The school production; - Training courses; - Holidays; - The last boy scout; - Have a break before you have a break down; - Sports day; - In the exam hall; - Marking madness; - Surviving a hangover; 6. Money's too tight to mention; - Money mis-management; - Day-tripping - or lack of it; - Extra-curricula spending; 7. Dealing with colleagues; - Gossip; - Being sporty; - When your classroom is used and abused; 8. Dealing with parents; - Parents' evening; - Letters from parents; - The school run; Conclusion
Associated web site: www.rantingteacher.co.uk.
Keywords: Teaching -- Anecdotes